Selected cytokine and chemokine concentrations in equine autologous conditioned serum are similar under defined and practically relevant storage conditions - Roth, Susanne Pauline; Liso, Giulia; Brehm, Walter; Wagner, Bettina; Schnabel, Christiane Liliane; Troillet, Antonia (Frontiers in Veterinary Science, 2025)
BackgroundThe anti-inflammatory and regenerative effects of autologous conditioned serum (ACS) in joint-associated disorders are presumably mediated by the biomolecules it contains, such as cytokines and chemokines. ACS is commonly used in equine practice after storage. Data regarding the influence of storage conditions of ACS on cytokine and chemokine concentrations are not available.ObjectivesTo evaluate the effect of commonly used storage conditions on selected cytokine and chemokine concentrations in equine ACS.MethodsFrom 10 horse patients with clinically indicated ACS preparation six ACS aliquots each were stored under different storage conditions. The samples were evaluated after storage at room temperature (rt) or at refrigerator temperature (6–8°C) for 6 h. Another set of samples was stored frozen at −20°C for 7 months. After this storage under clinically relevant conditions all samples were frozen at −80°C, and compared to an aliquot immediately frozen at −80°C. Mediator concentrations were determined by fluorescent bead-based multiplex assays using monoclonal antibodies that are specific for the respective analyzed molecule: interferon (IFN)-γ, interleukin (IL)-17A, IL-4, IL-10, and IFN-α (equine cytokine 5-plex assay) as well as CC-chemokine ligand 2 (CCL2), CCL3, CCL5, CCL11, tumor necrosis factor (TNF)-α, and IL-1β (equine chemokine 6-plex assay) were analyzed.ResultsConcentrations of IFN-γ and IL-10, as well as the chemokines analyzed, showed marked interindividual differences. The cytokines IL-17A, IL-4, and IFN-α were not detected in any of the samples analyzed. Concentrations of selected cytokines, and chemokines were similar between the defined storage conditions.ConclusionsConcentrations of selected cytokines, chemokines, and IL-1ra in equine ACS were not influenced by the defined storage conditions studied (rt, refrigerated, frozen).